Efektivitas Penggunaan Kahoot Sebagai Alat Evaluasi Pembelajaran IPAS Materi Rantai Makanan di Sekolah Dasar - Lutfiah, Siti Lulu; Oktaviani, Qori; Salsabila, Shifa; Heryadi, Yadi (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to analyze the effectiveness of the use of Kahoot! as an evaluation tool for learning science on food chain materials, especially in improving student understanding of concepts, motivation, and involvement. The research method used is qualitative with data collection through observation, interviews, and document analysis in an elementary school that implements Kahoot! in learning evaluation. The results of the study show that Kahoot! has succeeded in significantly increasing student motivation and participation, but its effectiveness in supporting an in-depth understanding of the concept of the food chain is still limited. Use of Kahoot! tend to encourage quick answers that sometimes ignore conceptual understanding and cause visual overload and digital fatigue in students. These findings underscore the need for a learning approach that combines Kahoot! with reflective strategies and the active role of teachers to maximize their benefits. In conclusion, Kahoot! It is a useful evaluation tool if it is properly integrated with the characteristics of the material and the cognitive needs of students, so as to be able to improve the quality of learning evaluation holistically. This research makes an important contribution to the development of adaptive and meaningful digital assessments in primary education.